Do novel insecticides pose a threat to beneficial insects?. Issue 1935 (30th September 2020) - Siviter, Harry; Muth, Felicity
Abstract : Systemic insecticides, such as neonicotinoids, are a major contributor towards beneficial insect declines. This has led to bans and restrictions on neonicotinoid use globally, most noticeably in the European Union, where four commonly used neonicotinoids (imidacloprid, thiamethoxam, clothianidin and thiacloprid) are banned from outside agricultural use. While this might seem like a victory for conservation, restrictions on neonicotinoid use will only benefit insect populations if newly emerging insecticides do not have similar negative impacts on beneficial insects. Flupyradifurone and sulfoxaflor are two novel insecticides that have been registered for use globally, including within the European Union. These novel insecticides differ in their chemical class, but share the same mode of action as neonicotinoids, raising the question as to whether they have similar sub-lethal impacts on beneficial insects. Here, we conducted a systematic literature search of the potential sub-lethal impacts of these novel insecticides on beneficial insects, quantifying these effects with a meta-analysis. We demonstrate that both flupyradifurone and sulfoxaflor have significant sub-lethal impacts on beneficial insects at field-realistic levels of exposure. These results confirm that bans on neonicotinoid use will only protect beneficial insects if paired with significant changes to the agrochemical regulatory process. A failure to modify the regulatory process will result in a continued decline of beneficial insects and the ecosystem services on which global food production relies.